Effectiveness and cost-effectiveness of interferon beta and glatiramer acetate in the UK Multiple Sclerosis Risk Sharing Scheme at 6 years: a clinical cohort study with natural history comparator. Issue 5 (May 2015) - Palace, Jacqueline; Duddy, Martin; Bregenzer, Thomas; Lawton, Michael; Zhu, Feng; Boggild, Mike; Piske, Benjamin; Robertson, Neil P; Oger, Joel; Tremlett, Helen; Tilling, Kate; Ben-Shlomo, Yoav; et al.
Summary Background In 2002, the UK's National Institute for Clinical Excellence (NICE) concluded that interferon beta and glatiramer acetate would be cost effective as disease-modifying therapies (DMTs) for multiple sclerosis only if the short-term disability benefits reported in clinical trials were maintained. The UK Multiple Sclerosis Risk Sharing Scheme (RSS) was established to assess whether disability progression was consistent with a cost-effectiveness target of £36 000 per quality-adjusted life-year projected over 20 years. We aimed to evaluate the long-term effectiveness and cost-effectiveness of these DMTs by comparing a cohort of patients with relapsing-remitting multiple sclerosis enrolled in the UK RSS with a natural history cohort from British Columbia, Canada. Methods In our clinical cohort we included patients starting a DMT who were enrolled in the UK RSS who had relapsing multiple sclerosis at baseline and had at least one further clinical assessment. In our control cohort we included patients in the British Columbia multiple sclerosis database (BCMS; data collection 1980–96) who met the same eligibility criteria as for the RSS cohort. We compared disability progression at 6 years for RSS patients with untreated progression modelled from BCMS patients using continuous Markov and multilevel models. The primary outcomes were the progression ratio (treated vs untreated) measured both in Expanded Disability Status Scale (EDSS) score and utility. A ratio of less than 100% for EDSS implied slower than expected progression on treatment compared with off treatment; a utility ratio of 62% or less implied that the DMTs were cost effective. Findings 5610 patients starting a DMT were enrolled in the UK RSS between Jan 14, 2002, and July 13, 2005 (72 sites), of whom 4137 were included in our clinical cohort. We included 898 BCMS patients in the control cohort who met the RSS inclusion criteria and had at least one EDSS score after baseline. RSS patients had a mean follow-up of 5·1 years (SD 1·4). Both models showed slower EDSS progression than predicted for untreated controls (Markov model, 75·8% [95% CI 71·4–80·2]; multilevel model, 60·0% [56·6–63·4]). Utility ratios were consistent with cost-effectiveness (Markov model, 58·5% [95% CI 54·2–62·8]; multilevel model, 57·1% [53·0–61·2]). Interpretation Findings from this large observational study of treatment with interferon beta or glatiramer acetate provide evidence that their effects on disability in patients with relapsing-remitting multiple sclerosis are maintained and cost effective over 6 years. Similar modelling approaches could be applied to other chronic diseases for which long-term controlled trials are not feasible. Funding Health Departments of England, Wales, Scotland, and Northern Ireland, Biogen Idec, Merck Serono, Bayer Schering Pharmaceuticals, Teva Pharmaceuticals Industries, UK National Institute of Health Research's Health Technology Assessment Programme.